2008
DOI: 10.1016/j.cub.2007.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Induced Receptor Endocytosis in a Novel Knockin Mouse Reduces Tolerance and Dependence

Abstract: Opioid drugs, such as morphine, are among the most effective analgesics available. However, their utility for the treatment of chronic pain is limited by side effects including tolerance and dependence. Morphine acts primarily through the mu-opioid receptor (MOP-R) , which is also a target of endogenous opioids. However, unlike endogenous ligands, morphine fails to promote substantial receptor endocytosis both in vitro, and in vivo. Receptor endocytosis serves at least two important functions in signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(126 citation statements)
references
References 32 publications
11
115
0
Order By: Relevance
“…It has been shown previously that MOR mutants engineered to undergo morphineinduced internalization demonstrate reduced propensity to cause these adaptive responses in heterologous cells (9). Also, mice expressing these mutant receptors show reduced morphine tolerance and dependence (33). Here, we have identified a naturally occurring variant that undergoes internalization with morphine without showing changes in morphine potency.…”
Section: Identification Of Variantsmentioning
confidence: 76%
“…It has been shown previously that MOR mutants engineered to undergo morphineinduced internalization demonstrate reduced propensity to cause these adaptive responses in heterologous cells (9). Also, mice expressing these mutant receptors show reduced morphine tolerance and dependence (33). Here, we have identified a naturally occurring variant that undergoes internalization with morphine without showing changes in morphine potency.…”
Section: Identification Of Variantsmentioning
confidence: 76%
“…In the case of opioids, for example, a strong correlation between tolerance or dependence and receptor endocytosis (relative activity versus endocytosis) has been proposed (Alvarez et al, 2001). In detail, Kim et al (2008) reported recently that mice transgenetically expressing a mutant of the -opioid receptor, which is in contrast to the wild-type receptor prone to morphine-induced endocytosis resist the development of morphine tolerance. These data highlight the correlation between tolerance and receptor endocytosis and indicate that knowledge about agonist-promoted receptor endocytosis provides useful information to interpret or predict the actions of a given drug in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested, therefore, that strategies that result in enhanced internalization of the MOP receptor in response to morphine might be useful in limiting the development of tolerance (Finn and Whistler, 2001) without compromising analgesia (Koch et al, 2005). This concept has recently received substantial support following production of a knockin line of mice in which the MOP receptor was replaced by a variant in which a substantial region of the C-terminal tail of the MOP receptor was exchanged for the equivalent sequence from the ␦ opioid peptide receptor (Kim et al, 2008). Such C-terminally modified forms of the MOP receptor had been shown previously to internalize in response to morphine when expressed heterologously and to limit the appearance of biochemical markers associated with the development of tolerance to morphine (Finn and Whistler, 2001).…”
mentioning
confidence: 99%